2011
DOI: 10.1371/journal.pone.0020164
|View full text |Cite
|
Sign up to set email alerts
|

Diosgenin, a Steroidal Saponin, Inhibits Migration and Invasion of Human Prostate Cancer PC-3 Cells by Reducing Matrix Metalloproteinases Expression

Abstract: BackgroundDiosgenin, a steroidal saponin obtained from fenugreek (Trigonella foenum graecum), was found to exert anti-carcinogenic properties, such as inhibiting proliferation and inducing apoptosis in a variety of tumor cells. However, the effect of diosgenin on cancer metastasis remains unclear. The aim of the study is to examine the effect of diosgenin on migration and invasion in human prostate cancer PC-3 cells.Methods and Principal FindingsDiosgenin inhibited proliferation of PC-3 cells in a dose-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
102
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(110 citation statements)
references
References 51 publications
2
102
0
1
Order By: Relevance
“…The proteolytic degradation of ECM, a major event in metastasis is mediated by extracellular proteases such as MMPs. MMPs play an important role in various pathologic processes such as angiogenesis and tumor invasion (Kahari and Saarialho-Kere, 1999;Chen et al, 2011). The chief MMPs that are involved in metastasis, MMP-2 and MMP-9 play a crucial role in prostate cancer progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proteolytic degradation of ECM, a major event in metastasis is mediated by extracellular proteases such as MMPs. MMPs play an important role in various pathologic processes such as angiogenesis and tumor invasion (Kahari and Saarialho-Kere, 1999;Chen et al, 2011). The chief MMPs that are involved in metastasis, MMP-2 and MMP-9 play a crucial role in prostate cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Gallic acid was also reported to inhibit the levels of ERK1/2, the key molecules of the ERK signaling pathway that has been shown to promote tumor invasion and metastasis (Liu et al, 2011). Diosgenin, a naturally occurring steroidal saponin present in a variety of plants including fenugreek (Trigonella foenum graecum) and roots of wild yam (Dioscorea villosa) was observed to inhibit metastasis by inhibiting MMPs and ERK1/2 (Chen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Taxol (a produce from Taxus brevifolia) is a mitotic inhibitor, used in the treatment of breast cancer, lung cancer and ovarian cancer. Similarly, diosgenine (Dioscorea deltoidea and Trigonella foenum graecum) inhibits migration and invasion of human prostate cancer PC-3 cells by reducing matrix metalloproteinases expression (Chen et al 2011). It is also used for the commercial synthesis of cortisone, pregnenolone, progesterone, and other steroid products.…”
Section: Future Perspectivementioning
confidence: 99%
“…The partial synthesis of steroids from plant based precursors is a boon because of the increasing demand for corticosteroids, contraceptives, sex hormones and anabolic steroids since 1960 (Hall and Walker 1991). Recent studies have found that diosgenin has been used in traditional medicine as an antihypercholesterolemia, antihypertriacylglycerolimia antihyperglycemic agent (Chen et al 2011) To date, diosgenin and related steroidal sapogenins were commercially obtained from the tubers of various Dioscorea species; however it is crucial to discover new and alternative sources of these compounds due to decreasing plant resources as well as increasing demand (Savikin et al 1998).…”
Section: Introductionmentioning
confidence: 99%